Ultrasound-Assisted Lactic Acid Fermentation of Bakraei (Citrus reticulata cv. Bakraei) Juice: Physicochemical and Bioactive Properties - Seyed Mohammad Bagher Hashemi; Dornoush Jafarpour; Elena Roselló Soto; Francisco J. Barba (Fermentation, 2022)
In this study, ultrasonication (US) (50 W, 30 kHz, 1–6 min) was used to increase the efficiency of Limosilactobacillus reuteri PTCC 1655 fermentation process (37 °C; 30 h) of Bakraei juice. Total sugars, pH, Brix, organic acids, vitamin C, polyphenols, antioxidant activity, α-amylase inhibition and anti-inflammatory properties were measured during the fermentation period. The results showed that by increasing the ultrasound time up to 5 min, pH, vitamin C, citric acid, and polyphenolic compounds decreased, while lactic acid, antioxidant capacity, α-amylase inhibition and anti-inflammatory properties were increased. When the ultrasound time was increased up to 6 min, compared to the non-ultrasound-treated sample, the efficiency of the fermentation process decreased and promoted a decrease in the microbial population, lactic acid levels, antioxidant activity, α-amylase inhibition, and anti-inflammatory properties of the juices. The initial anti-inflammatory activity (11.3%) of juice reached values of 33.4% and 19.5%, after US treatments of 5 and 6 min, respectively, compared to the non-sonicated juice (21.7%), after 30 h of fermentation. As a result, the use of ultrasound in the controlled fermentation process can increase the efficiency of fermentation process.